2016
DOI: 10.1021/acs.langmuir.6b01851
|View full text |Cite
|
Sign up to set email alerts
|

Iron Ion and Iron Hydroxide Adsorption to Charge-Neutral Phosphatidylcholine Templates

Abstract: Surface-sensitive X-ray scattering and spectroscopy techniques reveal significant adsorption of iron ions and iron-hydroxide (Fe(III)) complexes to a charge-neutral zwitterionic template of phosphatidylcholine (PC). The PC template is formed by a Langmuir monolayer of dipalmitoyl-PC (DPPC) that is spread on the surface of 2 to 40 μM FeCl3 solutions at physiological levels of KCl (100 mM). At 40 μM of Fe(III) as many as ∼3 iron atoms are associated with each PC group. Grazing incidence X-ray diffraction measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…The adsorption isotherms and fitting results are shown in Figures a, S3, and S4 and Table S2. Compared with the Freundlich isotherm, the Langmuir isotherm could better describe the adsorption behaviors with all R 2 > 0.99, implying the monolayer adsorption of CR onto the adsorbents surface . The maximum adsorption capacity of Fe­(OH) 3 @Cellulose PHFs was calculated to be 689.65 mg/g, much higher than those of conventional Fe­(OH) 3 powder (44.11 mg/g, Figure S3) and pure spun cellulose fibers (200.81 mg/g, Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…The adsorption isotherms and fitting results are shown in Figures a, S3, and S4 and Table S2. Compared with the Freundlich isotherm, the Langmuir isotherm could better describe the adsorption behaviors with all R 2 > 0.99, implying the monolayer adsorption of CR onto the adsorbents surface . The maximum adsorption capacity of Fe­(OH) 3 @Cellulose PHFs was calculated to be 689.65 mg/g, much higher than those of conventional Fe­(OH) 3 powder (44.11 mg/g, Figure S3) and pure spun cellulose fibers (200.81 mg/g, Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…For example, more condensed films are commonly observed for simple fatty acids with ionic subphases compared to pure water subphases (Brzozowska et al, 2013; Petty, 1996). Wang et al have reported similar responses for dipalmitoyl phosphatidylcholine monolayers on the Fe 3+ subphase, where films were condensed in the liquid expanded (LE) phase as the Fe 3+ subphase concentration was increased (Wang et al, 2016). As noted above, the subphase pH is approximately two orders of magnitude smaller than the bulk solution pKa 1 (which corresponds to protonation of the nitrogen head group) for the surfactant.…”
Section: Resultsmentioning
confidence: 84%
“…The association of trivalent ions with surfactant molecules is more complex compared to most mono‐ or divalent ions (e.g., see (Aroti et al, 2004; Shah and Schulman, 1965) and the references therein) in part because of the potential for forming coordinate covalent bonds between the transition metal ions and surrounding ligand molecules in bulk solution (Tyrode and Corkery, 2018; Wang et al, 2014, 2016; Wen et al, 2016). More broadly, interactions between trivalent ions, and iron in particular, with charged surfactant interfaces is of interest because of their importance in membrane‐based biomineralization processes, as well as their relevance in controlling the interaction between metal‐based nanomaterials and self‐assembled ionic surfactants that comprise nanoparticle coatings (Arakaki et al, 2003; Kang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in DNA charge neutralization and condensation between hydrolysed and classical cations can be explained by their different DNA binding of the multivalent counterions and pH regulation. The capillary electrophoresis and the spectroscopic results for the Fe(III) complexes with DNA in aqueous solution showed that Fe(III) binds to the backbone phosphate group at low cation concentration, while at higher Fe(III) content, there are chelations via major groove and the phosphate group and no major perturbations of the base pairs, while Fe(III) causes DNA condensation, and no DNA conformational changes occurred upon Fe(III) complex formation, and DNA remains in the B-form [28,29,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fe(III) and La(III), both in oxidation state +3, can exist in aqueous solution as ions or as complexes. The two ions show their quite distinctive behavior in solutions, as it was found that La 3+ provides a reasonably close representation of a “classical” ion, that is, one whose interaction is dominated by standard statistical mechanics, while Fe 3+ , with the same valence and very similar radius, provides an extreme case of specificity in which interactions with the hydrophilic groups are driven by the formation of reversible covalent bonds [28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%